Analisis kepuasan Masyarakat Terhadap Pelayanan BPJS Makassar dengan Menggunakan Metode Importance Perfomance Analysis (IPA) - nfn Rosmini (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2019)
This study aims to analyze the satisfaction of participants or users of BPJS on the quality of BPJS service quality in Makassar. Respondents in this study were drawn from the Makassar Community who were registered as BPJS participants in Makassar, which amounted to 1.2 million people. The samples selected in this study were 384 respondents with 5% precision. Research data obtained through survey respondents by distributing questionnaires. Data processing and analysis using the Importance Performance Analysis (IPA) method and using the help of the SPSS program.The results showed that the satisfaction of BPJS participants or users of BPJS performance and services at the Hospital had not reached expectations of what was considered important by BPJS users or participants. This can be seen from the total suitability level of 72.11% which is still less than the maximum level of customer satisfaction that is 100% and the attributes that need to be considered in each quadrant are quadrants A, B, C, and quadrant D for further enhance BPJS performance against BPJS participants. From the results of this study, the BPJS program should pay more attention to the performance of its services, especially in hospitals by ignoring the attributes in quadrant A whose priorities are very high but the performance or performance obtained is still very poor.